Coverage-Oriented Reliability of Wireless Sensor Networks with Multistate Nodes - Chakraborty, Suparna (Curtin University, 2021)
To quantify the flow-oriented reliability and coverage-oriented reliability of WSNs with multistate nodes, this thesis proposes new metrics: WSN Reliability (WSNRel), Area-Coverage Reliability (ACR) and Coverage-oriented Reliability (CORE). WSNRel provides a minimal-path based approach to evaluate flow-oriented reliability of WSNs with multistate nodes. The metrics, ACR, and CORE, aim at quantifying the coverage-oriented capability of a WSN. To quantify ACR and CORE, Monte Carlo simulation approaches that utilize an energy matrix are presented.